Family of Bistable Attractors Contained in an Unstable Dissipative Switching System Associated to a SNLF - J. L. Echenausía-Monroy; J. H. García-López; R. Jaimes-Reátegui; D. López-Mancilla; G. Huerta-Cuellar (Complexity)
This work presents a multiscroll generator system, which addresses the issue by the implementation of 9-level saturated nonlinear function, SNLF, being modified with a new control parameter that acts as a bifurcation parameter. By means of the modification of the newly introduced parameter, it is possible to control the number of scrolls to generate. The proposed system has richer dynamics than the original, not only presenting the generation of a global attractor; it is capable of generating monostable and bistable multiscrolls. The study of the basin of attraction for the natural attractor generation (9-scroll SNLF) shows the restrictions in the initial conditions space where the system is capable of presenting dynamical responses, limiting its possible electronic implementations.